1216 Intrauterine Growth Restriction and Developmental Programming of Renal Disease. (October 2012) - Vedovato, S; Visentin, S; Cosmi, E; Cavallin, F; Mion, M; Zaninotto, M; Trevisanuto, D; Zanardo, V
Abstract : Background and Aims: Intrauterine growth restriction (IUGR) complicated by umbilical artery vasculopathy may have adverse effects on integrity and function of vascular endothelium and has been associated to atherosclerosis and to glomerulosclerosis risk in adulthood. Aortic intima media thickening, a preclinical sign of atherosclerosis, has been documented from intrauterine life, whereas the first signs of glomerulosclerosis have not been determined. So the aim of this study was to compare albuminuria/creatiniruria ratio (ACR) in IUGR and appropriate for gestational age (AGA) neonates. Methods: A prospective cohort study has been performed on 25 IUGR consecutive fetuses evaluated at Department of Woman and Child Health of Padua University between December 2009 and December 2010. They were considered IUGR if the estimated fetal weight (EFW) was below 10th percentile and the umbilical artery pulsatility index (PI) > 2 standard deviations. Each IUGR newborn was matched with 2 controls AGA neonates, of the same gestational age ± 1 week. They were considered AGA if the EFW was between 10th and 90th percentile. A urine sample was collected at 24–72 hours after birth for ACR determination. Results: Among the 25 IUGR fetuses enrolled, 2 were excluded because 1 had trisomy 21 and 1 renal agenesis. The remaining 23 were matched with 46 AGA newborns. ACR was significantly higher in IUGR compared to AGA newborns: median (IQR) 183.0 (113.6–264.7) vs 122.8 (72.5–191.9); p=0.04. Conclusions: IUGR is associated with significantly greater albuminuria at birth. This may be an early marker of glomerulosclerosis, which leads to renal disease in adulthood.